2021
DOI: 10.3389/fsufs.2021.734088
|View full text |Cite
|
Sign up to set email alerts
|

The “Sweet Spot” in the Middle: Why Do Mid-Scale Farms Adopt Diversification Practices at Higher Rates?

Abstract: In the past few decades, farmers and researchers have firmly established that biologically diversified farming systems improve ecosystem services both on and off the farm, producing economic benefits for farmers and ecological benefits for surrounding landscapes. However, adoption of these practices has been slow, requiring a more nuanced examination of both barriers and opportunities to improve adoption rates. While previous research has demonstrated that both individual and structural factors shape farmers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Similar patterns were found for cover crops with a hotspot in the more marginal farmland of Monterey County. A study of farms across 20 counties in Indiana found that cover cropped fields were significantly steeper than non-cover cropped fields, likely for erosion control, and that farms that cover cropped were often smaller (Lira and Tyner, 2018), much like the mid-sized farms in our region that have reported using similar diversification practices (Esquivel et al, 2021). This was also supported in our interviews where many farmers reported maintaining hedgerows/windbreaks and cover crops in hilly or less prime farmland to prevent erosion.…”
Section: Patterns Of Adoptionsupporting
confidence: 74%
See 3 more Smart Citations
“…Similar patterns were found for cover crops with a hotspot in the more marginal farmland of Monterey County. A study of farms across 20 counties in Indiana found that cover cropped fields were significantly steeper than non-cover cropped fields, likely for erosion control, and that farms that cover cropped were often smaller (Lira and Tyner, 2018), much like the mid-sized farms in our region that have reported using similar diversification practices (Esquivel et al, 2021). This was also supported in our interviews where many farmers reported maintaining hedgerows/windbreaks and cover crops in hilly or less prime farmland to prevent erosion.…”
Section: Patterns Of Adoptionsupporting
confidence: 74%
“…Within our interview sample, farms ranged in size from 4 acres to over 10,000 acres (mean: 1,935 acres; median: 100 acres) and spanned four counties: Monterey (5 interviews), San Benito (4), Santa Cruz (5), and Santa Clara (1), with 5 additional farmers spanning multiple of these counties. Details of participant recruitment and interview procedures can be found in Esquivel et al (2021) and Carlisle et al (2022). Briefly, we selected a stratified sample of all organic farms in these counties that listed organic lettuce as a crop and contacted farmers that reflected ecological diversity (e.g., crop diversity) and a diversity of farm scales (i.e., sizes), geographical locations within the study region, and cultural backgrounds/first languages.…”
Section: Qualitative Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Farmers explained in open responses on the survey that this was because expanding into new market channels added to operational logistics and required a greater investment of time and resources to manage, a phenomenon detailed by Bachman et al (2021) . As noted by Esquivel et al (2021) , each market channel came with its own buyer requirements in terms of food safety protocols. These varying standards were likely exacerbated during the pandemic when greater sanitation protocols were put in place.…”
Section: Discussionmentioning
confidence: 99%